Semiotic Landscapes: Scaling Indonesian Multilingualism - Zane Goebel (Humaniora, 2020)
This article presents a very preliminary description of a sample of photos of signage (e.g. posters, signs, billboards) drawn from around six hundred photos taken in Bandung in January 2019. Drawing upon scholarship on value and scale in general, and work on semiotic landscapes in particular, this paper seeks to extend earlier analysis of multilingual signage in Indonesia. I explore how an analysis of this signage can provide insights into multilingualism, inequality, and mobility in Indonesia, as well as how different social, political, and economic regimes effect the multilingual landscape.